2021
DOI: 10.3390/nu13020353
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Poor Nutrient Intakes and Food Insecurity on the Psychological Distress among Community-Dwelling Middle-Aged and Older Adults during the COVID-19 Pandemic

Abstract: This study aimed to investigate the impact of food insecurity and poor nutrient intake on the psychological health of middle-aged and older adults during the COVID-19 pandemic. A sub-sample of 535 individuals aged 52 years and above, from the earlier cohort and interventional studies (n = 4) from four selected states in Peninsular Malaysia, were recruited during the COVID-19 outbreak (April to June 2020). Telephone interviews were conducted by trained interviewers with a health sciences background to obtain pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
1
20
1
Order By: Relevance
“…From the studies included in the review, food insecurity or insufficiency was linked to mental health problems and general wellbeing of individuals consistent with studies elsewhere, which have demonstrated that food insecurity is a significant factor associated with psychological distress among middle-aged and older adults [45]. One of the studies reported that moderate and severe food insecurity significantly increased psychological distress outcomes among both men and women, but this effect was greater with increase in age [36].…”
Section: Impact Of Food Insecurity and Insufficiency On Mental Health Outcomessupporting
confidence: 68%
“…From the studies included in the review, food insecurity or insufficiency was linked to mental health problems and general wellbeing of individuals consistent with studies elsewhere, which have demonstrated that food insecurity is a significant factor associated with psychological distress among middle-aged and older adults [45]. One of the studies reported that moderate and severe food insecurity significantly increased psychological distress outcomes among both men and women, but this effect was greater with increase in age [36].…”
Section: Impact Of Food Insecurity and Insufficiency On Mental Health Outcomessupporting
confidence: 68%
“…During the COVID‐19 outbreak, the prevalence of FI levels among the elderly population was lower (14.8%) 32 than in a previous study, which found that 27.7% of older respondents had FI 33 . According to this study, a potential explanation for this outcome could be that most of the respondents were living with their families during the MCO and that, since they were working from home, the children were able to provide adequate and nutritious meals for their parents 32 . In a previous study, Rohida et al .…”
Section: Food Insecurity's Consequences and Nutritional Outcomes In The Malaysian Populationcontrasting
confidence: 59%
“…It was obligatory for patients who needed physiotherapy to direct their treatment to home-based applications, but their treatment was interrupted during the restriction period. In a study conducted in patients with Parkinson's, it was found that depressive thoughts of patients who could not receive physical therapy increased and their treatment was disrupted during the pandemic [55].…”
Section: Resultsmentioning
confidence: 99%